Kekuasaan, Jarak dan Kesantunan: Suatu Analisis Fungsional dalam Teks - Gusnawaty, Gusnawaty (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2009)
Politeness in expression according to Brown and Levinson (1978/1987); Leech (1983); and Ide (1989) is very important to notice in social life in order to avoid conflict which may occur in communication. Yet, politeness is applied differently in different culture because each utterance cannot be apart from its context (Leech, 1983). The goal of this study is to examine the politeness strategies in text that implemented in Complaint Letters which is published in “Harian Fajar” daily. Functional Analysis with focus on Field, Tenor, and Mode of Text is used to analyze the data. The analysis shows that power, distance and deference influence the text and strategy choices. The strategic choices indicate there is a distance in communication between interlocutors.